Oak Processionary Moth in the United Kingdom. (1st February 2013) - Townsend, Mark
There seems to be a constant stream of bad news stories relating to the introduction of pests, weeds and diseases to new environments. The inadvertent transport of flora and fauna by man across borders, and the subsequent introduction of alien species into new habitats is not a new problem. In recent years, the rise in international trade, and especially in the horticultural industry, has seen a paralleled increase in the risk of introducing harmful organisms. In the last 6 years, Thaumetopoea processionea (Oak Processionary Moth) (OPM), Anoplophora glabripenni (Asian Longhorn Beetle) and Chalara fraxinea (the fungus causing causing Ash Dieback) have all been imported into the UK on nursery stock or shipping packing material. Oaks (Quercus spp.) in the UK are under threat from Agrilus biguttatus (buprestid beetle), acute and chronic oak decline, both with complex causes, and the introduction of OPM to the UK in 2006 has only served to increase the stress on this iconic tree of the British landscape. OPM is a member of the Lepidoptera order of insects, from the Thaumetopoeidae family which includes T. pityocampa (Pine Processionary Moth, PPM), T. pinivora (Eastern Pine Processionary Moth) and T. bonjeani (Cedar Pocessionary Moth). The larvae will feed on many Quercus spp and a high population can lead to complete defoliation of trees with a resulting fall in subsequent growth and vigour. This can have a financial impact on timber growers. Furthermore, the larvae have toxic hairs which can cause serious health problems.